Border Lines: The Partition of Judaeo-Christianity. By Daniel Boyarin. Pp. xviii + 374. (Divinations: Rereading Late Ancient Religion). Philadelphia: University of Pennsylvania Press, 2004. isbn 0 8122 3764 1. £25.50/38.50 - Dunn, James D. G. (The journal of theological studies, 2006)
How and when did ‘the parting of the ways’ between Judaism and Christianity take place? The old questions are still on the agenda in many seminars on the New Testament, early Christianity, and early Judaism. Some think that the impact of Jesus, his death and resurrection, were sufficient in themselves to pull the two apart. Indeed, if early Christian apocalyptic means that Christianity was seen from the beginning to have emerged on a quite different plane, then any heilsgeschichtlich continuity with Israel of old can be set aside as a claim made by Paul's Jewish-Christian opponents (as Lou Martyn argues).